2012
DOI: 10.1093/carcin/bgs005
|View full text |Cite
|
Sign up to set email alerts
|

ZEB2 upregulates integrin α5 expression through cooperation with Sp1 to induce invasion during epithelial–mesenchymal transition of human cancer cells

Abstract: Epithelial-mesenchymal transition (EMT) is a process implicated in tumor invasion, metastasis, embryonic development and wound healing. ZEB2 is a transcription factor involved in EMT that represses E-cadherin transcription. Although E-cadherin downregulation is a major event during EMT and tumor progression, E-cadherin reduction is probably not sufficient for full invasiveness. The mechanisms by which E-cadherin transcriptional repressors induce mesenchymal genes during EMT remain largely unknown. Here, we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 42 publications
3
62
1
Order By: Relevance
“…Lu et al have shown that miRNA-19a, which is associated with cancer invasion and metastasis and is expressed highly in gastric cancer cell lines, induces EMT in gastric cancer cells by activating the PI3K/AKT signal pathway (33 (12). Previous study by Nam and colleagues on cancer cell EMT has shown that Sp1 plays crucial roles in the integrin α5-dependent induction of EMT and metastasis (8). Given these findings, we sought to determine whether Sp1 is involved in the EMT of gastric cancer, and whether abnormal expression of Sp1 in gastric cancer EMT, invasion and metastasis is regulated in a post-transcriptional manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lu et al have shown that miRNA-19a, which is associated with cancer invasion and metastasis and is expressed highly in gastric cancer cell lines, induces EMT in gastric cancer cells by activating the PI3K/AKT signal pathway (33 (12). Previous study by Nam and colleagues on cancer cell EMT has shown that Sp1 plays crucial roles in the integrin α5-dependent induction of EMT and metastasis (8). Given these findings, we sought to determine whether Sp1 is involved in the EMT of gastric cancer, and whether abnormal expression of Sp1 in gastric cancer EMT, invasion and metastasis is regulated in a post-transcriptional manner.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer growth and metastasis, Sp1 influences a variety of cancer cell types through the regulation of oncogenes, tumor suppressor genes, cell cycle regulators, growth related signal transduction pathways, angiogenic factors and apoptosis (5,6). Sp1 is expressed at high levels in many cancers (7) and is closely associated with EMT (8,9). New therapies targeting Sp1 could, therefore, represent beneficial additions to current clinical chemotherapy strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, there are reports that ZEB2 can act as a transcriptional activator when complexed with SP1, driving the expression of vimentin and integrin α-5 in certain cancer cell lines without directly binding DNA (Bindels et al, 2006;Nam et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Several transcription factors have been characterized as transcriptional repressors of E-cadherin and are implicated in promoting EMT in tumor progression: the Snail superfamily of zinc-finger factors (Snail and Slug), the ZEB family (ZEB1 and ZEB2) and basic helix-loop-helix factors (Twist, E47 and TCF4) (Li et al, 2011;Nam et al, 2012). The mechanisms through which these repressors downregulate E-cadherin and other epithelial genes during EMT are fairly well established.…”
Section: Discussionmentioning
confidence: 99%